Degradasi Zat Warna Rhodamin B menggunakan Katalis TiO2 dengan Metode Fotosonolisis - Wenti Aulia; Hary Sanjaya (Departemen Kimia FMIPA UNP, 2023)
Research has been carried out on the degradation of Rhodamine B dye with TiO2 as a catalyst using the photosonolysis method. The purpose of this study was to determine the optimum time and optimum mass of the TiO2 catalyst used to degrade rhodamine B. The results of the percentage degradation of rhodamine B were obtained from the absorbance value measured using a UV-Vis spectrophotometer. The maximum wavelength of rhodamine B obtained from the measurement of the UV-Vis spectrophotometer is 553.8 nm. The results showed that the optimum time to degrade rhodamine B was 210 minutes with a degradation percentage of 95.39%. On the effect of increasing the mass of TiO2 catalyst, the optimum mass of TiO2 is 0.05 grams with a degradation percentage of 93.44%.